HUBUNGAN KONFLIK TERHADAP PROFESIONALITAS KERJA GURU UPT SMPN 10 TAPUNG KABUPATEN KAMPAR - Sri Agustina Ratnawati; Ria Rafianti, Refli Surya Barkara, Muhammad Afrillyan Dwi Syahputra (CV. ADIBA ASIHA AMIRA, 2024)
The purpose of this study is to determine the relationship between work conflict and teacher professionalism in schools, particularly its impact on the quality of individual and organizational performance. Poorly managed work conflicts can disrupt professionalism, such as by reducing commitment, hindering collaboration, or lowering adherence to work standards. Conversely, a high level of professionalism can be a key factor in resolving work conflicts constructively, as professionalism includes the ability to communicate effectively, maintain work ethics, and prioritize shared interests. Therefore, the author is interested in examining the topic